Status And Effects Of Food Provisioning on Ecology of Assamese Monkey (Macaca Assamensis) In Ramdi Area of Palpa, Nepal - Adhikari, Krishna; Khanal, Laxman; Chalise, Mukesh Kumar (Journal of Institute of Science and Technology, 2018)
The population status of Assamese monkey (Macaca assamensis) (McClelland 1840) and its interaction with the local people is poorly documented in Nepal. In 2014, we studied the population status, diurnal time budget and human-monkey conflict in Ramdi, Nepal by direct count, scan sampling and questionnaire survey methods, respectively. Two troops of Assamese monkey having total population of 48 with the mean troop size of 24 individuals were recorded in the study area. The group density was 0.33 groups / km² with a population density of 6 individuals/ km². The male to female adult sex ratio was 1:1.75 and the infant to female ratio was 0.85. The provisioned troop of Assamese monkey in Ramdi spent less time in feeding and movement while higher time was invested in resting and grooming than the nonspecific populations in the wild habitats. The human-monkey conflict is high in Ramdi, primarily due to the crop-raiding from fields and even the storage; the major crops raided are maize, vegetables, pulses and fruits. The higher reproductive success in terms of infant to adult female ratio, increased human-monkey conflicts and lesser investment of the diurnal time in foraging and feeding by Assamese monkey troop of Ramdi might be associated with the food provisioning. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018, Page: 183-190